Educational Democracy in the Perspective of Islamic Education Philosophy - Azwar, Boyke; Salminawati, Salminawati; Usiono, Usiono (Bulletin of Science Education, 2023)
This paper explains the concept of educational democracy in the perspective of Islamic educational philosophy. Although democracy and Islamic education may seem contradictory at first glance, an in-depth study reveals the fundamental compatibility between the two. In Islam, education is seen as a basic right of every individual, similar to the basic principles of democracy that emphasize freedom and human rights. In this context, educational democracy is not only about access, but also about how education is delivered and how education-related decision-making processes are carried out. Islamic educational philosophy emphasizes the importance of justice, equality and recognition of diversity, principles that are in line with democratic ideas. This article suggests that by integrating democratic principles into the Islamic education system, a more inclusive, participatory and just approach to education can be achieved. Thus, educational democracy in the perspective of Islamic philosophy of education represents a paradigm that values diversity, participation, and justice in education. Keywords: Educational Democracy, Islamic Education, Philosophy Perspective